Improvement of Piezoresistive Properties of Suspended Single‐Walled Carbon Nanotube Arrays via Selective Trimming. (2nd May 2019) - Zheng, Fuzhong; Hu, Guangzhong; Liu, Zhongbin; Wu, Chenguang; Zhang, Jie; Yang, Xing; Zhou, Zhaoying; Wu, Ying; Kuang, Shuangyang
Abstract: An efficient procedure for the fabrication of highly force‐sensitive aligned and suspended primitive single‐walled carbon nanotube (SWNT) devices is developed. First, an array of individual ultra‐long SWNTs is grown by chemical vapor deposition and suspended between two adjacent Au electrodes adhered on a breakable Si wafer. Armchair metallic SWNTs and low‐resistivity quasi‐metallic SWNTs are then selectively removed from the suspended SWNT array to upgrade the electromechanical mechanism of this type of sensitive device by strain‐based electrical burn‐off. Second, energy band and thermoelectronic emission theories in semiconductor physics are combined to calculate and analyze the effect of the length of the suspended SWNT on the aforementioned burn‐off method. The increase in length of the suspended SWNT section facilitates the easy electromechanical characteristic optimization of the suspended SWNT array. Moreover, the suspended SWNT array has a strong electromechanical response after strain‐based electrical burn‐off with sensitivity (gauge factor) of more than 600, linearity of less than 8.27%, and no hysteresis. Finally, the thermal effect is discussed in terms of this analytical method and experimental results. Abstract : A suspended single‐walled carbon nanotube (SWNT) array is developed via selective trimming to improve its piezoresistive properties by burning off low‐resistance and low‐strain‐sensitivity SWNTs in an ≈1300 µε stretched state under uniaxial deformation. Theoretical calculation showing the highest resistance differences for a 10 µm long SWNT array suggests that the best improvement of its piezoresistive sensitivity is when quasi‐metallic SWNTs with high gauge factor are retained.